Building on indigenous knowledge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Pacific Agroforestry: An Information Kit. CTA-EU-Pacific Regional Agricultural Programme co-publication. 1999. 200 pp. ISBN 982 343 038 1 CTA number 975. 40 credit points